2019
DOI: 10.1111/andr.12607
|View full text |Cite
|
Sign up to set email alerts
|

A new system of sperm cryopreservation: evaluation of survival, motility, DNA oxidation, and mitochondrial activity

Abstract: BackgroundSperm vitrification (V) is a method for cryopreservation, without the use of conventional cryoprotectants, by plunging the sperm suspension directly into liquid nitrogen (LN25).ObjectiveThis study aimed to compare the new system of V with conventional freezing (CF) protocol using fresh spermatozoa as reference (C).Material and methodsProspective cohort study. A total of 47 sperm samples from men attending the infertility clinic at Instituto Valenciano de Infertilidad Valencia. The sperm V solution wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…It was demonstrated that conventional freezing resulted in higher motility and viability, while spermatozoa undergoing vitrification were healthier regarding morphology and had fewer defects of sperm head, midpiece and tail [32]. Very recently, Pabon et al [33] used 47 human sperm samples to compare the efficiency of vitrification and conventional freezing protocols. They found vitrification was optimal for sperm cryopreservation as vitrification protocol resulted in better motility recovery and higher mitochondrial activity [33].…”
Section: Is Vitrification Superior To Conventional Freezing?mentioning
confidence: 99%
“…It was demonstrated that conventional freezing resulted in higher motility and viability, while spermatozoa undergoing vitrification were healthier regarding morphology and had fewer defects of sperm head, midpiece and tail [32]. Very recently, Pabon et al [33] used 47 human sperm samples to compare the efficiency of vitrification and conventional freezing protocols. They found vitrification was optimal for sperm cryopreservation as vitrification protocol resulted in better motility recovery and higher mitochondrial activity [33].…”
Section: Is Vitrification Superior To Conventional Freezing?mentioning
confidence: 99%
“…Cryopreservation of spermatozoa is an important technology of reproductive medicine [1,2]. Since data on the cryopreservation of human spermatozoa in the presence of cryoprotectants were first published in the late 1950s [3], several cryopreservation methods have been introduced, including conventional freezing and vitrification (cryopreservation by direct plunging into liquid nitrogen) techniques [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It was noted the high effectiveness of technology for cryoprotectant-free vitrification by direct dropping of human spermatozoa suspension into liquid nitrogen [6,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, three cryopreservation methods are used including slow freezing, rapid freezing and vitrification. Since slow freezing is time consuming with the need for an expensive programmable freezer, research activities have increasingly been oriented towards the rapid freezing and vitrification methods in recent years [1]- [5]. Rapid freezing and vitrification are also superior to slow freezing in preserving sperm motility and DNA integrity [5]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since slow freezing is time consuming with the need for an expensive programmable freezer, research activities have increasingly been oriented towards the rapid freezing and vitrification methods in recent years [1]- [5]. Rapid freezing and vitrification are also superior to slow freezing in preserving sperm motility and DNA integrity [5]- [10]. In particular, rapid freezing and vitrification rely only on non-permeating cryoprotective agents (CPA), including natural sugars such as sucrose and trehalose, for sperm cryopreservation omitting the harmful effects of permeating CPA such as glycerol on human sperm [3] [4] [11] [12].…”
Section: Introductionmentioning
confidence: 99%